2020
DOI: 10.30935/ijpdll/8439
|View full text |Cite
|
Sign up to set email alerts
|

Learning Evaluation of Mathematics during the Pandemic Period COVID-19 in Jakarta

Abstract: This research aims to evaluate the learning of mathematics at the college level conducted through distance learning programs during the COVID-19 pandemic in Jakarta. This research is a type of evaluation research using the Context, Input, Process, and Product (CIPP) model that is (1) context consists of program background and program planning (2) Inputs include of students readiness, teaching materials, facilities and infrastructures (3) process consisting of teaching methods and constraints in learning, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
0
15
1
12
Order By: Relevance
“…Many students worldwide do not have access to distance learning or even just to read reading resources (Bakker & Wagner, 2020;Engelbrecht et al, 2020;Morgan, 2020;Sá & Serpa, 2020). In Indonesia, such a problem is also present (Bahasoan, Ayuandiani, Mukhram, & Rahmat, 2020;Febrianto et al, 2020;Hebebci, Bertiz, & Alan, 2020;Kamsurya, 2020;Mailizar et al, 2020). However, in this study, only the teachers from rural areas reported the problem.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Many students worldwide do not have access to distance learning or even just to read reading resources (Bakker & Wagner, 2020;Engelbrecht et al, 2020;Morgan, 2020;Sá & Serpa, 2020). In Indonesia, such a problem is also present (Bahasoan, Ayuandiani, Mukhram, & Rahmat, 2020;Febrianto et al, 2020;Hebebci, Bertiz, & Alan, 2020;Kamsurya, 2020;Mailizar et al, 2020). However, in this study, only the teachers from rural areas reported the problem.…”
Section: Resultscontrasting
confidence: 52%
“…However, in this study, the teachers prioritise their students' mental health to maintain their immunity to the virus. It follows Kamsurya (2020) findings, stating that people should support and increase the immune system to avoid the coronavirus.…”
Section: Resultsmentioning
confidence: 99%
“…Any innovative and groundbreaking methodological proposal, such as the one presented in this research work, can be implemented in other subjects, universities, and countries if the appropriate circumstances are fulfilled. Possible barriers include the lack of material or economic means, such as those detected by Mohammadi, Mohibbi, and Hedayati [96] in the establishment of HELMS (Higher Education Learning Management System) in Afghanistan, or the preparation, facilities, and infrastructure available for the teaching staff responsible for online teaching as reported by Kamsurya [97]. Another aspect to highlight for this approach to materialize in other classrooms is the need for coordination between schools or faculties, students, and professors [98], always bearing in mind the opinion and needs of the students [99].…”
Section: Discussionmentioning
confidence: 99%
“…Pentingnya TPACK menurut Manfra & Spires (2013) yakni TPACK merupakan berbagai domain pengetahuan guru yang harus dimiliki untuk mengintegrasikan TIK secara efektif. TIK yang digunakan oleh guru untuk pembelajaran online selama pandemi Covid-19 dalam penelitian Basilaia & Kvavadze (2020), Gao & Zhang (2020), Henaku (2020), Jadhav, Bagul, & Aswale (2020, Jariyah & Tyastirin (2020), Jena (2020), Kamsurya (2020), Lie, Tamah, Gozali, Triwidayati, Utami, & Jemadi (2020), Rajhans, Memon, Patil, & Goyal (2020, dan Rap, Maggor, Aviran, Serebro, Easa, Yonai, Waldman, & Blonder (2020) diantaranya adalah media apps, google classroom, google hangouts meet, MOOC, chaoxing, whatsapp, telegram, zoom meeting, schoology, kaizala, youtube, podcast, teamlink, e-mail, educational channel on tv, video conferencing tools, dedicated educational portals and social, dan powerpoints. Sedangkan di Indonesia sendiri menurut Lie et al (2020) sebagian besar masih menggunakan media sosial whatsapp group (WAG) saja dengan presentase sebesar 84%.…”
Section: Pendahuluanunclassified